Lost in space : Architecture and Dementia - Feddersen, Eckhard; Lüdtke, Insa (Birkhäuser, 2014)
How can we provide good spatial orientation for people with dementia? This question is addressed extensively in a selection of professional essays and projects that also carve out specific requirements for various disciplines. The book is a useful guide to all disciplines involved in design and planning but also to friends and family memebers.